Quranic-Based Character Education: Ethical Communication in the Digital Era - Alfriani, Ranti Dwi; Andriani, Yuli; Armadila, Armadila; Khairul, Mohd. (Al-kayyis: Journal of Islamic Education, 2025)
Communication in human life is a fundamental aspect of social interaction. The concept of communication is not only related to effective communication methods, but also to communication ethics. Communication ethics, which includes aspects such as honesty, gentleness, and the use of appropriate language, is an important foundation for social interaction among Muslims. This study aims to explore how the principles of communication ethics found in the Quran can be applied in everyday life in the modern era. This study uses a qualitative method with a content analysis approach by collecting and analyzing primary data in the form of Quranic verses related to communication ethics as well as secondary data from relevant books, articles, and papers. The results show that the Quran teaches various principles of civilized, honest, polite, and responsible communication, such as qaulan sadidan, qaulan ma'rufa, qaulan layyina, qaulan baligha, qaulan karima, and qaulan maisura. By prioritizing positive and constructive content and conducting tabayyun before disseminating information, individuals can contribute to more ethical and productive communication in this digital age.